Acute Hemodynamic Effects of Virtual Reality-Based Therapy in Patients of Cardiovascular Rehabilitation: A Cluster Randomized Crossover Trial - Alves da Cruz, Mayara Moura [UNESP]; Ricci-Vitor, Ana Laura [UNESP]; Bonini Borges, Giovanna Lombardi [UNESP]; Silva, Paula Fernanda da [UNESP]; Ribeiro, Felipe [UNESP]; Marques Vanderlei, Luiz Carlos [UNESP] (Elsevier B.V., 2020)
Objective: To analyze the acute hemodynamic effects of adding virtual realityebased therapy (VRBT) using exergames for patients undergoing cardiac rehabilitation (CR). Design: Crossover trial. Setting: Outpatient rehabilitation center. Participants: Patients (N=27) with a diagnosis of cardiovascular disease or cardiovascular risk factors. Mean age (years) +/- SD was 63.4 +/- 12.7 and mean body mass index (kg/m(2)) +/- SD was 29.0 +/- 4.0. Interventions: Patients performed 1 VRBT session and 1 CR session on 2 nonconsecutive days. Each session comprised an initial rest, warm-up, conditioning, and recovery. During warm-up, in the VRBT session, games were performed with sensors to reproduce the movements of avatars and, in the CR session, patients were required to reproduce the movements of the physiotherapists. In the conditioning phase for VRBT, games were also played with motion sensors, dumbbells, and shin guards. The CR session consisted of exercises performed on a treadmill. The intensity of training was prescribed by heart rate reserve (HRR; 40%-70%). Main Outcome Measures: The primary outcomes were heart rate, blood pressure, respiratory rate (RR), rating of perceived exertion (RPE), and peripheral oxygen saturation, evaluated before, during, and after the VRBT or CR session on 2 nonconsecutive days. The secondary outcome was to evaluate whether the patients achieved the prescribed HRR and the percentage of time they maintained this level during the VRBT session. Results: VRBT produces a physiological similar pattern of acute hemodynamic effects in CR. However, there was greater magnitude of heart rate, RR, and RPE (P<.01) during the execution of VRBT and until 5 minutes of recovery, observed at the moments of rest, and 1, 3, and 5 minutes of recovery. Conclusions: Although the VRBT session produces similar physiological acute hemodynamic effects in CR, greater magnitudes of heart rate, RR, and RPE were observed during its execution and up to 5 minutes after the session. (C) 2020 by the American Congress of Rehabilitation Medicine
Keywords: Blood pressure; Cardiac rehabilitation; Cardiovascular diseases; Exercise; Exposure therapy; Heart rate; Rehabilitation; Virtual reality